Analisis Pembiayaan IB Muamalat Multiguna pada Skim Murabahah di Bank Muamalat Cabang Gorontalo - Nasila, Rahmat; Zainuddin, Yusran (Madani: Jurnal Pengabdian Ilmiah, 2020)
IB Muamalat Multipurpose Financing is a consumptive financing which is very much needed by the community. This study aims to determine a procedure in having multipurpose iB Muamalat financing and to know the steps taken to minimize the risk of financing iB Muamalat Muiltiguna. Multipurpose iB Muamalat Financing can be obtained by purchasing halal goods. For that we need a research method in the form of interview and observation methods. Direct methods can be obtained by prospective customers by interviewing and observing at the time of filing for financing. From several procedures the bank has the right to provide financing or refuse financing proposed by a prospective customer. Whether or not a prospective customer is eligible for this financing depends on the bank's assessment and whether in the future the prospective customer can return the financing to avoid financing risks.